Pediatric and adolescent chronic myeloid leukemia: A follow-up study in Western India - Sangita A. Vanik; Dhaval Jetly; Biren Parikh; Karthik Dhandapani; Rukmini Bezbaruah (Indian Journal of Pathology and Microbiology)
Background: Chronic myeloid leukemia (CML) is relatively rare in pediatric and adolescent age groups. The purpose of this study was to evaluate the clinical, hematopathological, and biochemical parameters of CML in pediatric and adolescent age groups, along with an assessment of the treatment response with first-line tyrosine kinase inhibitors (TKI) and its correlation with the prognostic scoring systems of adults. Materials and Methods: A retrospective study of 44 Breakpoint Cluster Region-Abelson leukemia virus (BCR-ABL1)-positive pediatric and adolescent CML cases registered at our hospital was done. The clinical and laboratory parameters were evaluated using hospital software. The treatment response was monitored and scoring was performed using mathematical calculations. Results: The mean age was 11.6 (±4.7) years. The median hemoglobin was 8.4 g/dL and 63.6% of the cases showed white blood cell (WBC) counts >250,000/μL. The average follow-up was 21 months. A total of 97.7 and 78.1% cases achieved complete hematological response (CHR) and molecular response, respectively, during the treatment course. The maximum number of patients had low Sokal and European treatment and Outcomes Study (EUTOS) scores. Seventy-five per cent of the cases achieved CHR at 3 months, while 73.6 and 78.6% CML-Chronic phase (CP) cases with low Sokal and EUTOS scores achieved CHR at 3 months, respectively. Conclusion: This study revealed that the CML cases in pediatric and adolescent age groups are normally present with higher WBC counts at the time of diagnosis. The association of the prognostic scoring system with treatment response was statistically insignificant. However, a larger cohort study is needed to determine the treatment response of TKI in children and adolescent CML and its correlation with the prognostic scoring systems.